Inland aquaculture development handbook - Blakely, David R. (Fishing New Books, 1989)
This comprehensive guide covers all aspects of extensive aquaculture, from the breeding of fish to the operation and management of an aquaculture business, in developing countries. Instead of dealing exclusively with the biological aspects of aquaculture - such as the life history of fish, breeding and rearing of young - this book covers the management of fish farms, including pond construction, water quality management, integrated aquaculture with pigs, poultry and agriculture, business-related subjects such as marketing and accounting, and extension and research support for development.